Pengaruh Musik Terhadap Kecemasan Ibu Selama Kangaroo Mother Care di Yogyakarta - Priliana Wiwi Kustio (Jurnal Keperawatan Notokusumo, 2013)
Background: Kangaroo Mother Care (KMC) is a means or method of caring for LBW, where there isdirect skin contact between mother and baby makes automatic adjustments to the mother's bodytemperature to protect her baby. Some interventions such as massage treatments in the NICU babies,Kangaroo MotherCare and listening to music has benefits to reduce maternal anxiety.